First book of atas of the conselho de Tui some thoughts - Fernandez, Manuel Torres (Seven Editora, 2023)
Steeped in history, the border city of Tuy is witness to the great episodes of relations between Spain and Portugal, while it houses within the walls the social relations of the Old Regime, in a specific local variant typical of Galicia